Students’ Response towards Cooperative Learning in English Classroom - Sitti Nurmila; Isna Humaera; Dewi Atikah (IAIN KENDARI, 2020)
This qualitative study aims to investigate the use of cooperative learning in English classroom based on students’ response at one of vocational schools in Kendari. The instruments used in this study were reflection and documentation with 36 students acted as the respondents who were chosen by using purposive sampling. The reflection guideline consists of five questions related to cooperative learning. This study reveals that the response of cooperative learning had positive response. Students’ reflection reveals that students are happy with cooperative learning, students found it easy to understand the material, and students could express their ideas analyzed based on the students’ reflection after learning process. This study implies that students’ response toward cooperative learning can help the students in learning foreign language. This approach helped them to acquire the knowledge through working in a team easily and made the learning process more interesting. The students also became more active to participate in the teaching and learning process.Key words: cooperative learning; English classroom; reflection; response.